Leveraging HR Analytics for Data-Driven Decision Making: A Comprehensive Review (International Journal of Food and Nutritional Sciences, 2022)
Human Resource (HR) Analytics has emerged as a critical tool for organizations to effectively manage their workforce and make informed decisions. This research paper aims to provide a comprehensive review of HR analytics, highlighting its importance, methodologies, benefits, and challenges. The paper explores the various applications of HR analytics in areas such as recruitment and selection, performance management, employee engagement, talent development, and retention. Additionally, it examines the key data sources, metrics, and analytical techniques used in HR analytics, including descriptive, predictive, and prescriptive analytics.